The Potential Effect of Dapagliflozin and Liraglutide in Attenuating Cardio-Renal Injuries in Diabetic Rats - Albanna AA; Ibrahim DA; Shamsher AM; Al-Shawia MA; Halboup A (Journal of Experimental Pharmacology)
Adel Ali Albanna,1 Doa’a Anwar Ibrahim,2 Amani Mohammed Shamsher,3 Mojahed Ali Al-Shawia,4 Abdulsalam Halboup1,5 1Department of Pharmacology, Faculty of Pharmacy, University of Science and Technology, Sana’a, Yemen; 2Department of Clinical Pharmacy and Pharmacy Practice, Faculty of Pharmacy, University of Science and Technology, Sana’a, Yemen; 3Department of Histopathology, University of Science and Technology Hospital, Sana’a, Yemen; 4Department of Biological Science, Faculty of Science, Sana’a University, Sana’a, Yemen; 5Discipline of Clinical Pharmacy, School of Pharmaceutical Science, Universiti Sains, Malaysia, Penang, MalaysiaCorrespondence: Doa’a Anwar Ibrahim, Department of Clinical Pharmacy and Pharmacy Practice, University of Science and Technology, Sana’a, Yemen, Email dr_d_anwar@hotmail.comObjective: To evaluate the therapeutic benefits of dapagliflozin and liraglutide as treatments for type 2 diabetes mellitus and their combined effects on T2DM-related complications, specifically cardio-renal injury.Methods: Thirty rats were randomly allocated into two groups, with the first group serving as the control group, which had 6 rats. The second group was the experimental group, which had 24 rats administered a high-fat diet for four weeks, followed by a single dose of streptozotocin (STZ) to induce diabetes mellitus (DM). This, combined with a high-fat diet, a low dose of STZ was used to cause sub-lethal damage to beta cells. HFD/STZ is an easy method to successfully create a rat model resembling human T2DM, causing insulin resistance, but it does not fully capture the complexity of human T2DM. The experimental group was randomly divided into a positive control group, a liraglutide (0.4 mg/kg, s.c) group, a dapagliflozin (1 mg/kg, orally) group, and a combination of Dapa and lira group, which were administered daily for four weeks. Blood samples were analyzed for glucose, insulin, and cardiac and kidney function markers. Cardiac and kidney tissue were examined to assess redox balance, glutathione (GSH), catalase (CAT), and malondialdehyde (MDA).Results: Dapa and/or lira administration improved the body weight, lipid profile, cardiac and kidney function markers. Furthermore, all treating groups exhibited restoration of the balance between oxidants and antioxidants. Histological studies also revealed a reduction in cardiorenal tissue injury caused by diabetes. Interestingly, the combined management of Dapa and Lira showed a more beneficial protective effect than individual treatments. This study uniquely explores the simultaneous impact on cardiac and renal systems in a diabetic model, offering novel insights into cardiorenal interaction and the combined therapeutic potential of Dapa and Lira.Conclusion: These findings suggest that the combination of dapagliflozin and liraglutide provides superior protection against diabetes-induced cardiorenal injury compared to either treatment alone, highlighting their potential as adjunctive therapies in reducing type 2 diabetes mellitus complications.Keywords: dapagliflozin, liraglutide, cardio-renal injuries